The Effectiveness of Prenatal Massage Therapy and Pregnancy Gymnastics Against Back Pain in Third Trimester Pregnant Women at Practice Independent Midwives in Bengkulu City - Kurnia Dewiani; Yetti Purnama; Linda Yusanti (JURNAL KEBIDANAN, 2022)
Back pain is the most common discomforts experienced by pregnant women in the third trimester. One of the non-pharmacological methods to overcome discomfort in the third trimester of pregnant women are prenatal massage and pregnancy exercise. Prenatal massage is a massage movement for pregnant women in the form of rubbing and pressing in such a way that does not stimulate contractions to reduce pain. Further, prenatal massage with a love pattern is different from ordinary massage which lies in movements in the form of love, butterfly, birth, and others as well as special points on the body. As a result, will increase relaxation and circulation. Pregnancy exercise is a form of exercise to strengthen and maintain the elasticity of the abdominal wall muscles, ligaments, and pelvic floor muscles associated with childbirth. This study aims to analyze the effect of prenatal massage therapy and pregnancy exercise on reducing back pain for pregnant women in the third trimester. The method was a quasi-experimental pre-post test with a control group design. The research subjects were third-trimester pregnant women with back pain complaints at the Independent Midwife Practice in Bengkulu City. The sampling technique was purposive sampling, divided into two groups using a simple random method. The group was conducted with 15 participants each for treatment (prenatal massage with love) and control (pregnancy exercise). Assessment of back pain was used a Visual Analogue Scale (VAS) questionnaire with a daily observation sheet. Statistical testing used Mann-Whitney analysis to analyze differences in the pre and post pain. In addition, the scales in each group with the significance of the test results were determined based on the p-value <0.05. The results show the p-value > =0.05 with the decision had no difference in the effect of prenatal massage and pregnancy exercise on back pain. Both interventions could reduce back pain in pre and post-intervention. In conclusion, the effects of giving prenatal massage with love pattern associated complaints of back pain in pregnant women in the third trimester.